STUDENTS’ LEARNING EXPERIENCES AND PSYCHOLOGICAL WELL-BEING: THE ROLE OF ACADEMIC STRESS AND SCHOOL SUPPORT - Suid Saidi; Surawardi Surawardi; Syaiful Bahri; Mubarak Mubarak; Yonathan Yonathan (Nurul Jadid University, 2026)
Student learning experiences and psychological well-being are important issues in education, particularly amidst increasing academic demands that impact students' mental health. However, qualitative studies linking learning experiences, academic stress, and social support are still limited. This study aims to explore students' learning experiences and their relationship to psychological well-being. The study used a qualitative approach through semi-structured interviews with three purposively selected students. Data were analyzed using thematic analysis and validated through triangulation and member checking. The results indicate that interactive learning increases student motivation and engagement; that academic stress elicits diverse psychological responses depending on coping strategies; and that social support from teachers and peers strengthens students' emotional stability and self-confidence. This study provides a more integrated qualitative empirical understanding of the relationship among these three factors. It serves as a basis for developing interactive learning strategies, managing academic stress, and strengthening social support to improve students' psychological well-being.